Immediate Results of Surgical Treatment of Patients with Strangulated of Ventral Hernia of the Anterior Abdominal Wall - Kh. Jafarov; I. Melnik (Asian Pacific Journal of Environment and Cancer, 2021)
The article presents results of treatment of 116 patients with strangulated incisional hernias of the anterior abdominal wall. It has been shown that the mandatory treatment algorithm for this category of patients should include monitoring of intra-abdominal pressure with timely correction of the manifestations of the “abdominal compartment syndrome”. The incidence of postoperative complications was -21%, postoperative mortality -9.5%.